Solanum lycopersicum L. CGN15499 ... - GLIS Of The ITPGRFA (Centre for Genetic Resources, the Netherlands, 2017)
Plant Genetic Resource. Taxonomy: Solanum lycopersicum L. Common name(s): tomato Other names: Sub Arctic Midi Conserved by: Centre for Genetic Resources, the Netherlands (CGN), Netherlands (Kingdom of the) Local sample unique identifier: CGN15499 Method of creation: Acquisition Date: 1993-08-12 Other identifiers: purl,http://purl.org/cgngenis/accenumb/CGN15499, n/a,1.1493 Historical: No Biological status: Advanced or improved cultivar MLS status: Not included ...